Управління діяльністю фахівців з кібербезпеки в умовах повномасштабного вторгнення - Мазник, Ліана Валеріївна; Двуліт, Зоряна Петрівна (My University, 2023)
Стаття присвячена дослідженню управління діяльністю фахівців з кібербезпеки в умовах повномасштабного вторгнення. Акцентовано, що кібербезпека вимагає технічної експертизи, розуміння загроз та ризиків, їх виявлення та запобігання кібератакам, дотримання етичних та правових стандартів. Зокрема, ідентифіковані ключові етичні аспекти, з якими стикаються фахівці з кібербезпеки. Дослідження підкреслює важливість навчання, вдосконалення навичок, диференціацію між особистісними навичками (soft skills) і адаптивними навичками (transferable skills), виявлення та реагування на кіберагресію та актуальність міжнародного співробітництва. Такий підхід сприяє забезпеченню безпеки організацій у сучасному інформаційному середовищі. Новизною дослідження є визначення змісту діяльності фахівців з кібербезпеки відповідно до основних концепцій кібербезпеки в умовах повномасштабної війни. Саме для таких фахівців визначена специфіка відповідних навичок в умовах впливу військових кіберризиків та інтенсифікації кіберзагроз. In this study dedicated to the management of cybersecurity professionals in the context of fullscale intrusion, significant aspects of this pressing issue have been examined. Drawing from an analysis of the content of cybersecurity professionals’ activities and their core concepts, it has been identified that this field encompasses various facets requiring diverse skills and knowledge from these experts. Specifically, cybersecurity experts must possess technical expertise, understand threats and risks, detect and thwart cyberattacks, and adhere to ethical and legal standards. Additionally, the ability to communicate and collaborate within a team, while considering socio-cultural and legal peculiarities of the country they operate in, is vital. In the context of full-scale intrusion, such as russia’s invasion of Ukraine in 2022, cybersecurity professionals face challenges of extraordinary complexity. They must respond to aggressive cyberattacks targeting various sectors, including governmental structures, critical infrastructure, media, and the information space. Simultaneously, they must consider ethical aspects and responsibly engage with other entities and organizations to ensure collective cyber defense. This research underscores the importance of adopting a comprehensive approach to managing cybersecurity professionals in times of intrusion. To achieve this, it is essential to provide training and continuous skill enhancement, establish effective mechanisms for detecting and responding to cyber aggression, and strengthen international cooperation in the field of cybersecurity. Through these measures, cybersecurity professionals will have the capability to effectively safeguard the interests of their organizations and nations amidst heightened cyber threats, ensuring the security, privacy, and rights of users. Such an approach contributes to creating a more resilient and secure information environment, a critical factor in the modern world. Furthermore, the article presents a comparative analysis of soft skills and transferable skills for cybersecurity professionals, highlighting key abilities and qualities crucial in this field. This analysis helps develop more effective strategies for training and developing cybersecurity experts, enhancing their professional competence to meet contemporary security demands. This analysis also promotes the improvement of managing cybersecurity professionals in the context of large-scale intrusion, emphasizing the importance of combining technical and interpersonal skills to ensure the reliability and effectiveness of cybersecurity.
Keywords: кафедра економіки праці та менеджменту; концепції кібербезпеки; кіберфахівці; особистісні навички; адаптивні навички; кіберзагрози; повномасштабне вторгнення; сybersecurity; conception of cybersecurity; cybersecurity professionals; soft skills; transferable skills; cyber threats; full-scale intrusion